Halide Perovskite Materials for Photo(Electro)Chemical Applications: Dimensionality, Heterojunction, and Performance. Issue 4 (5th May 2021) - Pan, Shuang; Li, Jun; Wen, Zhangchuan; Lu, Rong; Zhang, Qingcheng; Jin, Huile; Zhang, Lijie; Chen, Yihuang; Wang, Shun
Abstract: In recent years, halide perovskite materials have sparked intensive research, including their burgeoning development in the field of photo(electro)chemical catalysis. Halide perovskite materials are based on abundant and low‐cost elements with a rich structural composition and a variety of molecular and morphological dimensionalities. They possess versatile advantages over other photo(electro)catalytic materials owing to the facile adjustment of electronic properties via molecular and compositional engineering. Thus, the rapid development of perovskite photo(electro)catalysts in the past 4–5 years has opened up new opportunities for diverse photo(electro)chemical applications, ranging from photocatalytic organic reactions (e.g., chemical transformations, photopolymerization, and degradation) to solar‐to‐chemical fuel conversion (e.g., water splitting and CO2 reduction). This review aims to provide an up‐to‐date discussion on recent applications of halide perovskite photo(electro)catalytic materials, emphasizing their crystal and morphological dimensionality, synthetic methodologies, heterojunction structures, and fundamental structure‐activity relationships. Furthermore, current challenges and future research directions for the rational design of halide perovskite materials to boost their overall catalytic performance and stability are identified and envisaged respectively. Abstract : The burgeoning development in the field of photo(electro)catalysis based on halide perovskite materials is highlighted with a focus on their crystal and morphological dimensionality, synthetic methodologies, heterojunction structures, as well as fundamental structure–activity relationships. Perspectives on the urgent challenges and current opportunities of halide perovskite materials are also given to aid future photo(electro)catalytic energy utilization.